Comparison of multiple methods to measure maternal fat mass in late gestation(1)(2) - Marshall, Nicole E (Am J Clin Nutr, 2016)
Background: Measurements of maternal fat mass (FM) are important for studies of maternal and fetal health. Common methods of estimating FM have not been previously compared in pregnancy with measurements using more complete body composition models. Objectives: The goal of this pilot study was to compare multiple methods that estimate FM, including 2-, 3- and 4-compartment models in pregnant women at term, and to determine how these measures compare with FM by dual-energy X-ray absorptiometry (DXA) 2 wk postpartum. Design: Forty-one healthy pregnant women with prepregnancy body mass index (in kg/m(2)) 19 to 46 underwent skinfold thickness (SFT), bioelectrical impedance analysis (BIA), body density (D(b)) via air displacement plethysmography (ADP), and deuterium dilution of total body water (TBW) with and without adjustments for gestational age using van Raaij (VRJ) equations at 37–38 wk of gestation and 2 wk postpartum to derive 8 estimates of maternal FM. Deming regression analysis and Bland-Altman plots were used to compare methods of FM assessment. Results: Systematic differences in FM estimates were found. Methods for FM estimates from lowest to highest were 4-compartment, DXA, TBW((VRJ)), 3-compartment, D(b(VRJ)), BIA, air displacement plethysmography body density, and SFT ranging from a mean ± SD of 29.5 ± 13.2 kg via 4-compartment to 39.1 ± 11.7 kg via SFT. Compared with postpartum DXA values, Deming regressions revealed no substantial departures from trend lines in maternal FM in late pregnancy for any of the methods. The 4-compartment method showed substantial negative (underestimating) constant bias, and the air displacement plethysmography body density and SFT methods showed positive (overestimating) constant bias. ADP via D(b(VRJ)) and 3-compartment methods had the highest precision; BIA had the lowest. Conclusions: ADP that uses gestational age-specific equations may provide a reasonable and practical measurement of maternal FM across a spectrum of body weights in late pregnancy. SFT would be acceptable for use in larger studies. This trial was registered at clinicaltrials.gov as NCT02586714.